Cytokine-Mediated Crosstalk between Immune Cells and Epithelial Cells in the Gut - Mousumi Mahapatro; Lena Erkert; Christoph Becker (Cells, 2021)
Cytokines are small proteins that are secreted by a vast majority of cell types in the gut. They not only establish cell-to-cell interactions and facilitate cellular signaling, but also regulate both innate and adaptive immune responses, thereby playing a central role in genetic, inflammatory, and infectious diseases of the gut. Both, immune cells and gut epithelial cells, play important roles in intestinal disease development. The epithelium is located in between the mucosal immune system and the gut microbiome. It not only establishes an efficient barrier against gut microbes, but it also signals information from the gut lumen and its composition to the immune cell compartment. Communication across the epithelial cell layer also occurs in the other direction. Intestinal epithelial cells respond to immune cell cytokines and their response influences and shapes the microbial community within the gut lumen. Thus, the epithelium should be seen as a translator or a moderator between the microbiota and the mucosal immune system. Proper communication across the epithelium seems to be a key to gut homeostasis. Indeed, current genome-wide association studies for intestinal disorders have identified several disease susceptibility loci, which map cytokine signatures and their related signaling genes. A thorough understanding of this tightly regulated cytokine signaling network is crucial. The main objective of this review was to shed light on how cytokines can orchestrate epithelial functions such as proliferation, cell death, permeability, microbe interaction, and barrier maintenance, thereby safeguarding host health. In addition, cytokine-mediated therapy for inflammation and cancer are discussed.